Heterologous Expression and Evaluation of Novel Plasmodium falciparum Transmission Blocking Vaccine Candidates - de Jong, Roos M.; Singh, Susheel K.; Teelen, Karina; van de Vegte-Bolmer, Marga; van Gemert, Geert-Jan; Stone, Will J. R.; Locke, Emily; Plieskatt, Jordan; Theisen, Michael; Bousema, Teun; Jore, Matthijs M. (Frontiers in Immunology, 2022)
Malaria transmission blocking vaccines (TBV) aim to induce antibodies that are able to interrupt Plasmodium falciparum development in the mosquito midgut and thereby prevent onward malaria transmission. A limited number of TBV candidates have been identified and only three (Pfs25, Pfs230 and Pfs48/45) have entered clinical testing. While one of these candidates may emerge as a highly potent TBV candidate, it is premature to determine if they will generate sufficiently potent and sustained responses. It is therefore important to explore novel candidate antigens. We recently analyzed sera from naturally exposed individuals and found that the presence and/or intensity of antibodies against 12 novel putative surface expressed gametocyte antigens was associated with transmission reducing activity. In this study, protein fragments of these novel TBV candidates were designed and heterologously expressed in Drosophila melanogaster S2 cells and Lactococcus lactis. Eleven protein fragments, covering seven TBV candidates, were successfully produced. All tested antigens were recognized by antibodies from individuals living in malaria-endemic areas, indicating that native epitopes are present. All antigens induced antigen-specific antibody responses in mice. Two antigens induced antibodies that recognized a native protein in gametocyte extract, and antibodies elicited by four antigens recognized whole gametocytes. In particular, we found that antigen Pf3D7_0305300, a putative transporter, is abundantly expressed on the surface of gametocytes. However, none of the seven novel TBV candidates expressed here induced an antibody response that reduced parasite development in the mosquito midgut as assessed in the standard membrane feeding assay. Altogether, the antigen fragments used in this study did not prove to be promising transmission blocking vaccine constructs, however our findings provide new leads for studying gametocyte biology.